Water Supply Schemes, Community Capacity Building, And Pro-Agripreneurship Among Mbororo Households In Western Highland Of Cameroon - Mohtangongho, David Njewoh (Digital Repository of Theses - SSBM Geneva, 2025)
The study analyses the effects of water supply schemes and agriculture community capacity building on pro agripreneurship among the Mbororo households at the West and North West Region of Cameroon. Data used in the study was elicited through the survey questionnaire administered on a sample of 475 households who lives in the rural setting in the various areas. Cluster sampling approach was used in grouping proximity villages into four zones and purposive sampling technique was adopted in selecting the households. The objectives of the study were achieved empirically by relying on the maximum likelihood estimation techniques in general structural equation modelling; principal component analysis was used to construct the indexes, and ordinary least square estimation method for consistency test in the findings. The results show that water supply schemes have a significant positive effect on pro agripreneurship at 1% significant level. The results equally indicated that agriculture community capacity building has a significant effect on pro agriprenuership. The signicificant of the effect of water supply scheme and agriculture community capacity building on pro agripreneurship means that a 1 unit increase in the level of water supply schemes cause 38.8% surge in the level of pro agripreneurship while agriculture community capacity building on the other hand resulted to an increase in pro agripreneurship to the tune of 35.2%. The findings also show that community capacity building does not strengthen the contribution of water supply schemes on pro agripreneurship. The results equally indicated that there is no statistically significant mean difference in pro-agripreneurship between male-headed and female-headed Mbororo households in the western highland of Cameroon. Based on these findings, the study therefore recommends that policies aimed at promoting rural agripreneurship development among indigenous group should adopt an integrated approach of agriculture community capacity building programs and water supply schemes initiatives. Keywords: Community, Agripreneurship Sustainability, Inclusive Development, Cameroon.